The Formation of the Social Policy of the Federal Council of Churches - Piper, John F. (A journal of church and state, 1969)
John F. Piper, Jr.; The Formation of the Social Policy of the Federal Council of Churches, Journal of Church and State, Volume 11, Issue 1, 1 January 1969, Page